Active queue management with discrete sliding modes in TCP networks - Ignaciuk, Przemysław; Karbowańczyk, Michał (Polska Akademia Nauk, Wydział IV Nauk Technicznych, 2014)
In this paper, a new active queue management (AQM) algorithm for data traffic control in TCP/IP networks is developed. The algorithm design is based on the principles of discrete sliding-mode control. Unlike majority of earlier studies, the design procedure considers the effects of both non-negligible delay in transferring data and feedback information and unpredictable capacity variations. The switching function is selected to incorporate a delay compensation mechanism, which ensures efficient network operation even for large bandwidthdelay product connections. The proposed algorithm, implemented as a packet marking scheme, is tested in discrete event ns-2 simulator. The results show that the algorithm provides fast convergence to steady state after sudden, unanticipated capacity changes. By generating smaller overshoots, the proposed algorithm also allows for reducing buffer space requirements to avoid packet loss as compared to the benchmark AQM solutions.
Keywords: sliding-mode control; congestion control; active queue management (AQM); discrete-time control systems